Impact of gender, family and school on problem-solving ability and mathematics achievement - Singh, Laishram Nirtish; Singh, Laisom Sharmeswar; Thokchom, Jocyline (Intelektual Pustaka Media Utama, 2026)
This study examines the problem-solving ability and mathematics achievement of secondary school students. It explores how these variables relate to gender, type of family, school type, and locality of school. Using a descriptive correlational method, the study sampled 1,200 students from Manipur, India. The investigators employed two tools they developed- the problem-solving ability test in mathematics and the mathematics achievement test (MAT) to gather data. The findings reveal that most students exhibit average problem-solving ability and mathematics achievement levels, irrespective of gender, type of family or locality of school. However, school type significantly impacts performance, with 39% of private school students achieving average mathematics achievement scores, compared to 43% of government school students scoring below average. A moderate positive correlation was identified between problem-solving ability and mathematics achievement across all demographic groups. These results underscore problem-solving ability as a critical determinant of success in mathematics, with implications for educators and policymakers. The study highlights the need for interventions focused on enhancing students’ problem-solving ability to improve overall mathematics performance. Future research should explore additional variables and broader regional contexts to deepen understanding and inform targeted strategies. By addressing these dynamics, this study contributes to the development of more equitable and effective educational practices.